The Dead Sea Scrolls After Fifty Years : A Comprehensive Assessment - Flint, Peter W.,; VanderKam, James C., (Biblical Studies, Ancient Near East and Early Christianity - Book Archive pre-2000., 1999)
The Dead Sea Scrolls after Fifty Years is being published to mark the fiftieth anniversary of the discovery of the first scrolls at Qumran. The two-volume set contains a comprehensive set of cutting-edge articles on a wide range of topics that are archaeological, historical, literary, sociological, or theological in character. Since the discovery of the first scrolls in 1947 an overwhelming number of studies has been published. Now, half a century later, nearly all scrolls found have been published in critical editions, and scholars can begin to assess the true relevance of the scrolls for the study of the Bible, Second Temple Judaism, and Early Christianity. The contributors to these volumes form an international team of leading specialists in the field. They have written critical surveys of particular aspects of Dead Sea Scrolls research, focusing on significant developments, theories and conclusions, while also indicating directions for future study.